PASSENGERS PERCEPTIONS TOWARDS SERVICE QUALITY OF FSC OF AN LCC GROUP - Teguh I. Maulana; Taufiq Nur; Alvi Muhayat Syah (Universitas Mercu Buana, 2018)
The establishment of Batik Air as a Full-Service-Carrier (FSC) of Lion Air Group, a Low-Cost-Carrier group, marks a new development in the airline industry. LCC groups had started their move to serve a larger customer segment to increase their share in key markets. Previously the multi-brand strategy was only utilized by FSC groups as a response to the entry of LCC in the market. This study specifically tries to investigate the perception of passengers towards FSC within an LCC group. An online survey was conducted among the passengers of Batik Air in the last one year. 247 respondents were obtained resulting in a 67.1% response rate. SEM analysis was used to analyze the data. This study provides light in revealing how passengers perceive the service quality of FSC under an LCC group. The current results also clarify whether the service performances of such FSC align with the perceived services by its customer. This study contributes to the existing customer perception and strategic literature in the way that is among the first studies to investigate the perception of passenger a newly established FSC from an LCC group. The study includes implications for the low-cost airline group that plans to establish a full-service unit to maintain the level of service quality thus can succeed in attracting passengers within the intended market